Coffee Wilt Disease - Flood, Julie (CABI, 2014)
This is story of an African coffee farmer in Uganda who I interviewed at the start of the project at the end of 1999. This farmer had 1000 coffee trees on his 1-ha farm. He was earning US$1000 per annum from approximately 1000 kg of green coffee he produced from his field. He had a family of seven that included five children who ranged in age between 5 and 15 years. He did not hire any outside labour to assist with crop harvesting and processing, and he supplemented his income by intercropping his coffee field with bananas, which are stable food crop in the area. In 1997/1998, when the war started in the Democratic Republic of Congo (DRC), there was a lot of coffee trafficking through illegal boarder crossings from DRC to Uganda. The military personnel operating in the area were bringing into Uganda ripe and unripe coffee cherries for processing and sale or export from Uganda. During this time, a disease called coffee wilt disease became evident to the coffee-growing public along the routes used by the military personnel. Before this period, the disease had been identified in very limited areas and was a minor threat to the coffee sector. After this period in the first year alone, the disease affected more than 600 trees from the farmer’s field. In that year, the farmer’s production yield was reduced by half, and by the second year, these 600 trees were dead and needed uprooting. By 1999, the yield from the coffee farm had reduced from a peak of 1000 kg of green beans to 400 kg, representing a 60% decline in income for the farmer. In absolute terms, this represents a decline of income from US$1000 to US$400 per annum for the family of seven. The Common Fund for Commodities has the farmer as its main client; therefore, we have every reason to worry when we witness such disasters. This project was designed to try to mitigate some of the problems by assisting the farmer described above through teaching the farmer different methods of controlling the spread of the coffee wilt disease and introducing to the farmer new disease-resistant varieties of coffee. The Common Fund has walked this journey with farmers in DRC, Uganda, Tanzania and Ethiopia and stands witness to the challenges faced by these farmers. I am happy to say that most farmers now know how to identify the disease in its early stages and how to stop its rapid spread to other trees in the field. If the farmers had the knowledge in the early 1990s, which they now have today, I am confident that at least 50% of the coffee crops loses could have been avoided. Just to put the effects of the coffee wilt disease into context in terms of the value of coffee lost by the affected countries, you may wish to note that the affected countries export over US$1 billion worth of coffee every year. Thus, a 30% crop loss due to coffee wilt disease represents US$300 million lost income per year. In real terms, this amount represents 1 million children not having access to education, health care and sometimes basic food for survival. This project is a development lesson for policy makers who sometimes fail to appreciate the challenges encountered by farmers in the agricultural business. As Project Manager, I would like to sincerely thank all the coffee scientists, farmer group leaders and Extension Service staff who guided the smooth implementation of this project.